Representações sociais de discentes sobre universidade: um estudo psicossocial entre ingressantes do vestibular e da seleção ProUni - Silva, Tarcimária Rocha Lula Gomes da (2007)
Demand for access to higher education to put in test the education Brazilian system in view of the surplus of selective processes of public universities, people without option to pay their studies at this education level. In this context, it has arisen the University for All(Universidade para Todos)Program, the ProUni, from Ministry of Education - MEC, created by the Federal Government in 2004, and that it aims the granting of full and partial scholarships in private higher education institutions, graduate courses in sequential specific training, low-income Brazilians students who do not have higher-level degree. Created by the Provisional Measure No 213/2004 and institutionalized by Law No. 11096 of January 13, 2005, the ProUni offers, however, the exemption of some taxes to those institutions that join the program. This is one of the privileged time for the study of Social Representations by offering the researcher, a living laboratory, natural environment, the confrontation between the established and new. In time like this people are challenged to incorporate the new system to the pre-existing one, aiming it through a strangeness of what was so familiar. It is through this game of social forces that we developed the present study with 196 entering higher education, of these are 116 of selective vestibular system and 80 of the ProUni selective system. We opt by the procedures for data collection in order to have access to the circulating senses, in addition to the streamlined responses. With foundation in Abric, we perform the test the Free Association of Words, then analysed by the software and by EVOC Content of the type theme as Bardin. Besides, we require of the subjects, a writing on the study object university later analysed by the software ALCESTE. The results point out to a representation strongly rooted in social factors such as more traditional socio-cultural elements: the beliefs, values, the symbols. It is unique in both groups of subjects: among those entering by the selective ProUni system, there was a stronger anchor in that it does not make inquiries about the program. At the same time, there is a stronger presence of objectivation, entering the selective vestibular system in order that they explained with a value judgement on the programme. It is suggested further studies considering the embryonic state of social representation, as recent as the social purpose that triggered. It would be relevant even the replication of the same research with other people in order to strengthen the power of the theorising of empiria available